Population screening for spinal muscular atrophy: A mixed methods study of the views of affected families. Issue 2 (28th October 2016) - Boardman, Felicity K.; Young, Philip J.; Griffiths, Frances E.
Abstract : Autosomal recessive conditions are a significant health burden with few treatments. Population carrier screening has been suggested as a means to tackle them. Little is known about the views of affected families despite the potential for direct impacts on them. Data are presented on attitudes among families affected by Spinal Muscular Atrophy (SMA) toward two population screening programs, pre‐conception, and prenatal. Data were gathered through qualitative interviews (n = 36) and a survey (n = 337). Eighty‐two survey participants had SMA and 255 were family members. The majority were in favor of screening (75%). Reasons for supporting pre‐conception screening support were a belief that it would reduce SMA‐related terminations and raise awareness of SMA in the population. For prenatal screening, reasons for support included a belief in the importance of informed decision‐making and the need to reduce suffering. Key reasons for non‐support of pre‐conception screening included concerns about carrier stigmatization and social engineering. For prenatal screening, concerns focused on the collateral loss of high quality of life lives affected by SMA. This study highlights that those affected by SMA are predominantly in favor of screening, although pre‐conception screening is most favored. While family members and adults with SMA had largely consistent views, perceptions varied according to the severity (type) of SMA, with those affected by SMA type II the least likely to support screening. These findings suggest that screening for SMA is a complex issue for affected families, underscoring the need to consider and include their views when planning and implementing screening programs. © 2016 Wiley Periodicals, Inc.